Pengaruh Kompetensi Pedagogik Guru terhadap Motivasi Belajar Peserta Didik Di Madrasah Ibtidaiyah Muhammadiyah Labakkang - Srinawati, Risna; Achmad, Fatoni (MOMENTUM : Jurnal Sosial dan Keagamaan, 2021)
This study aims to determine: 1) How is the pedagogical competence of the Madrasah Ibtidaiyah Muhammadiyah Labakkang teachers, 2) How the learning motivation of students at Madarasah Ibtidaiyah Muhammadiyah Labakkang, and 3) How is the effect of teacher pedagogic competence on the learning motivation of students at Madarasah Ibtidaiyah Muhammadiyah Labakkang. This type of research is classified as quantitative with the approach used is the ex post facto approach. The population / sample of this study were low class students. Furthermore, the data collection method used was a questionnaire. Then, the data processing and analysis techniques used are descriptive statistical analysis and infrential statistical analysis. The results obtained in this study indicate that: 1) The pegagogical competence of teachers at Madrasah Ibtidaiyah Muhammadiyah Labakkang at intervals of 63 - 66 which is at a frequency of 9 or 22.5%. 2) The learning motivation of students at Madrasah Ibtidaiyah Muhammadiyah Labakkang is at intervals of 61 - 65, which is at a frequency of 20 or 50%. 3) There is a significant effect of teacher pedagogical competence on the learning motivation of students at Madrasah Ibtidaiyah Muhammadiyah Labakkang, it can be seen that based on the coeeficiens (α) table, thitung = 4.463 The t-table value can be searched for 1,684 so that comparing ttabel and thitung turns out that thitung = 4,463> ttabel = 1,684, so Ho is rejected and H1 is accepted so that there is an effect of pedagogic competence (x) on learning motivation (y) at Madrasah Ibtidaiyah Muhammadiyah Labakkang